1991
DOI: 10.1177/089826439100300402
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Psychotropic Medication Use in the Nursing Home

Abstract: The authors examined mental illness and psychotropic medications use among nursing home residents. Data were drawn from the Texas Long-Term Care Reimbursement Project, a 1986 study of nearly 2,000 residents in 49 nursing homes. The study measured the use of antipsychotics and other psychotropic medications, physical health conditions, mental illness diagnoses, behavior, and nursing and other direct-care time for sampled residents. The findings indicated that 45% of the sample was receiving an antipsychotic or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…Accordingly, a psychiatric diagnosis was not a general independent determinant of the use of psychotropics, if a determinant at all. Other studies have also documented that only a minor proportion of those receiving psychotropics have a supporting psychiatric diagnosis (Burns and Kamerow, 1988;Arling et al, 1991;Beardsley et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, a psychiatric diagnosis was not a general independent determinant of the use of psychotropics, if a determinant at all. Other studies have also documented that only a minor proportion of those receiving psychotropics have a supporting psychiatric diagnosis (Burns and Kamerow, 1988;Arling et al, 1991;Beardsley et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sta members were asked to give their assessment of the residents' mental status (dementia or other brain disorder, depression, other than depression and dementia, unknown and mentally well). Doane et al (1989) 4571 20 Thacker and Jones (1997) 382 23 Morgan et al (1982) 1122 34 Nygaard et al (1990) 1284 33 Beardsley et al (1989) 526 35 McGrath and Jackson (1996) 909 24 Studies on all psychotropics Arling et al (1991) The sta informant for a particular resident was the primary caregiver or one with similar knowledge of the resident, as selected by the other sta members. One hundred and eighteen sta members (median age 43 years) participated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Garrard et al (1991) con®rmed that in nursing homes, the documentation of reasons for prescribing neuroleptic drugs is poor. Arling et al (1991) showed that 37% of their sample had no mental illness or behaviour problems but were taking antipsychotics.…”
Section: Documentationmentioning
confidence: 98%
“…Other investigators have not presented the overall use of this group of medicines. However, if we compare the sums of the use of neuroleptics and tricyclic antidepressants in nursing homes in the present material with these studies taken together, 1,3,4,29–31 our figures are similar or lower.…”
Section: Discussionmentioning
confidence: 59%